Halal tourism in social science discipline: A literature review - Al Fauzi Rahmat (Universitas Negeri Yogyakarta, 2021)
Halal tourism is a new segment in tourism studies that have received attention and has now proliferated. Past studies have not been so deep in treading global scientific literature on halal tourism studies on tracking its evolution and trends among scientific journal which focuses on social science discipline. Therefore, this article is based on a systematic literature review analysis of halal tourism in social science discipline as an effort to improve our understanding of previous halal tourism studies. Data were obtained from the academic database Scopus, 31 articles were obtained about halal tourism in social science discipline, and the data period was collected from the beginning to the end of 2020. The data is illustrated using two applications, namely NVIVO and VOSViewer, as the primary tools for analyze qualitative data, which selected; (VOSViewer; Keyword Co-occurrence Network Maps and Trend (KCNM/T)), (NVIVO; Hierarchy Chart (HC), word frequencies (WF), and Explore Diagram Analysis (EDA)). The results showed that, from 31 journals, Stephenson (2014) has the most influence with high cited, besides, Tourism Management as a journal name that identified many articles published there, and Routledge as a publisher with a high total journal on Halal Tourism, and Indonesia as a country that high mention time. Specifically, various approaches and distributions based on methodology, objectives, and geography were the research's focus. Recent trends and the dominant frequency of words from the study of halal tourism have shown several scholars' high interest. In the halal tourism studies on social sciences discipline, previous scholars have carried out many different research segments, namely, tourism issues, product issues, destination issues, travel issues, service issues, and market issues. Future research is also considered in this article